A standardized methodology for the surveillance of antimicrobial prescribing linked to clinical indications in primary care. (11th September 2017) - Smith, Sue; Hawker, Jeremy I; Smith, Gillian E; Morbey, Roger; Johnson, Alan P; Fleming, Douglas M; Shallcross, Laura; Hayward, Andrew C
Abstract: Background: A key component of strategies to reduce antimicrobial resistance is better antimicrobial prescribing. The majority of antibiotics are prescribed in primary care. While many existing surveillance systems can monitor trends in the quantities of antibiotics prescribed in this setting, it can be difficult to monitor the quality of prescribing as data on the condition for which prescriptions are issued are often not available. We devised a standardized methodology to facilitate the monitoring of condition-specific antibiotic prescribing in primary care. Methods: We used a large computerized general practitioner database to develop a standardized methodology for routine monitoring of antimicrobial prescribing linked to clinical indications in primary care in the UK. Outputs included prescribing rate by syndrome and percentages of consultations with antibiotic prescription, for recommended antibiotic, and of recommended treatment length. Results: The standardized methodology can monitor trends in proportions of common infections for which antibiotics were prescribed, the specific drugs prescribed and duration of treatment. These data can be used to help assess the appropriateness of antibiotic prescribing and to assess the impact of prescribing guidelines. Conclusions: We present a standardized methodology that could be applied to any suitable national or local database and adapted for use in other countries.